Adaptation of the 4D Model in Developing a Competency Documentation Framework for ISO 9001:2015 Implementation in the Manufacturing Industry - Tiana Nur Rahmayanti; Edi Suryadi; Tutik Inayati; Rasto Rasto (Dinasti Publisher, 2025)
Effective competency documentation remains a critical challenge in implementing ISO 9001:2015 Clause 7.2 across Indonesian manufacturing industries, primarily due to the absence of a structured methodological framework. This methodological gap hinders the systematic and effective management of employee competencies. This study proposes an integrated competency documentation system through the adaptation of the 4D model (Define, Design, Develop, Disseminate) for ISO 9001:2015-certified manufacturing organizations. The research employed a development method encompassing Define, Design, and Develop stages, with data triangulation from document analysis, stakeholder interviews, and expert validation conducted in an automotive component manufacturing company. Validation involved two experts with complementary expertise and testing with multi-department employees. The results produced four integrated Standard Operating Procedures: formulation of competency standards, development of a competency matrix, planning of competency development, and evaluation of effectiveness. Expert validation indicated a score of 79.5% (categorized as good) with an inter-rater reliability of r = 0.94, while user trials yielded high levels of satisfaction. The system effectively addressed gaps in standard setting, employee competency mapping, systematic evaluation, and integrated documentation. The adaptation of the 4D model proved to be an effective approach for balancing standard compliance with operational needs, providing a practical contribution to ISO 9001:2015 implementation within the Indonesian manufacturing sector.